The basal nodosaurid ankylosaur Europelta carbonensis n. gen., n. sp. from the Lower Cretaceous (lower Albian) Escucha Formation of northeastern Spain. - James I Kirkland (Public Library of Science (PLoS), 2013)
Nodosaurids are poorly known from the Lower Cretaceous of Europe. Two associated ankylosaur skeletons excavated from the lower Albian carbonaceous member of the Escucha Formation near Ariño in northeastern Teruel, Spain reveal nearly all the diagnostic recognized character that define nodosaurid ankylosaurs. These new specimens comprise a new genus and species of nodosaurid ankylosaur and represent the single most complete taxon of ankylosaur from the Cretaceous of Europe. These two specimens were examined and compared to all other known ankylosaurs. Comparisons of these specimens document that Europelta carbonensis n. gen., n. sp. is a nodosaur and is the sister taxon to the Late Cretaceous nodosaurids Anoplosaurus, Hungarosaurus, and Struthiosaurus, defining a monophyletic clade of European nodosaurids- the Struthiosaurinae.